Increased antibiotic exposure in early life is associated with adverse outcomes in very low birth weight infants. Issue 9 (23rd September 2022) - Chen, Wen-Yin; Lo, Yu-Cheng; Huang, Po-Han; Chen, Yu-Xuan; Tsao, Pei-Chen; Lee, Yu-Sheng; Jeng, Mei-Jy; Hung, Miao-Chiu
Abstract : Background: The use of antibiotics in the early lives of premature infants may alter the microbiota and influence their clinical outcomes. However, whether the administration of probiotics can influence these outcomes remains unknown. In our study, probiotics were routinely administered unless contraindicated. We explored whether increased antibiotic exposure with the routine use of probiotics was associated with necrotizing enterocolitis (NEC) or bronchopulmonary dysplasia (BPD). Methods: A retrospective cohort study was conducted, enrolling very low birth weight (VLBW) infants admitted between January 1, 2016, and March 31, 2020, to a medical center. Days of antibiotic exposure in the first 14 days of life were recorded. The primary outcomes were NEC and BPD. Adjusted odds ratios (aORs) and 95% confidence intervals (CIs) were calculated using multivariable regression analyses to assess risk factors. Results: Of 185 VLBW infants admitted to the medical center, 132 met the inclusion criteria. Each additional day of antibiotic treatment was associated with increased odds of NEC (aOR, 1.278; 95% CI, 1.025-1.593) and BPD (aOR, 1.630; 95% CI, 1.233-2.156). The association remained in the NEC analysis after adjustment for probiotic use. Conclusion: Increased antibiotic exposure in the early lives of VLBW infants was associated with increased risks of NEC and BPD. The probiotics did not influence the outcomes. Our findings suggest that clinicians should be alerted to the adverse outcomes of antibiotic use in infants with VLBWs.